FULFILLMENT OF DISABILITY RIGHTS IN DAMRI BUS AND TRANS METRO DELI TRANSPORTATION SERVICES IN THE CITY OF MEDAN - Manalu, Dimpos; Pasaribu, Vera Asihna Riris; Saruksuk, Agus Krsitin; Gulo, Mutiara Wisda (Program Studi Sosiologi Universitas Malikussaleh, 2024)
This research aims: 1) to find out the rights of persons with disabilities are fulfilled in the Damri Bus and Trans Metro Deli Bus transportation services in Medan City; 2) to find out the constraints and barriers experienced by people with disabilities in accessing Damri Bus and Trans Metro Deli Bus transportation in the city. Research data was obtained using observation, interviews, documentation and focused group discussions. The results are as follows: Damri Bus and Trans Metro Deli Bus transportation is not yet disability friendly so that disability rights in public transportation services have not been fulfilled. A number of obstacles faced by people with disabilities include: narrow and high bus doors, damaged bus stops, sidewalks that are disjointed and do not lead to the bus stops, unavailability of braille letters, and unavailability of travel routes at each bus stop. And this is actually rooted in a policy-making paradigm that is not yet disability-friendly. However, in general, the Trans Metro Deli Bus service is still better and disabilities-friendly than the Damri Bus.